Dentoskeletal characteristics of non-syndromic pierre robin sequence and isolated incomplete cleft palate children: a retrospective case control study - Zhang, Xiang; Yang, Shuang; Yang, Xudong; Zhou, Zhibo (Frontiers in Pediatrics, 2025)
BackgroundPierre Robin sequence (PRS) is characterized by micrognathia, glossoptosis, and upper airway obstruction. This study aimed to compare the dentoskeletal characteristics of children diagnosed with non-syndromic PRS and those with cleft palate.MethodsThis study was conducted on the non-syndromic PRS patients in the database of our hospital. The control group of non-syndromic isolated incomplete cleft palate patients was matched from the same database by age, gender and weight in a 1:3 ratio. The dentoskeletal characteristics were compared between the PRS and control groups.ResultsThe study included 14 patients in the PRS group and 42 patients in the control group. A point-Nasion-B point (ANB) angle was significantly greater in the PRS group compared with the control group. The PRS group exhibited a significantly lower ratio of the linear distance between Articulare and Gonion (ArGo) to the distance between Gonion and Pogonion (GoPo) compared to the control group. Additionally, the anteroposterior length and area of the lower pharyngeal airway space (LPAS) were markedly reduced in the PRS group.ConclusionThe ANB angle, the ArGo/GoPO ratio and the anteroposterior length and area of LPAS could serve as valuable indicators to identify micrognathia in patients with non-syndromic PRS.